“We Don’t Want to Talk About It”: Building Trust for Difficult Decisions - Dezort, Steven; Palmer, Amitabha; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Clinical ethicists must be attuned to nonverbal cues and the deeper issues they raise and, if needed, be willing and agile to change course from discussing goals of care to establishing trust. We present a case study where a family and care team disagree about whether a lack of a do-not-resuscitate and do-not-intubate (DNR/DNI) order for a patient with a terminal prognosis is leading to medically justifiable and ethically defensible decisions. An ethicist called a family meeting to discuss the order but determined, after reading the family’s nonverbal cures, that establishing trust was first needed in order to have that discussion, and that such trust could be built by not discussing the order.